IT-Based Learning Management and Student Motivation in Resource-Constrained Elementary Schools: A Comparative Case Study from Indonesia - Mubarok, Ate Jamaludin; Helmawati, Helmawati (Journal of Innovation and Research in Primary Education, 2026)
The integration of Information and Communication Technology (ICT) in elementary education represents a critical strategy for enhancing learning quality, yet implementation in resource-constrained contexts remains underexplored. This study examined IT-based learning management implementation and its relationship to student learning motivation in elementary schools with limited infrastructure. A qualitative multiple case study was conducted at two elementary schools in Campaka District, Cianjur Regency, Indonesia. Data were collected through participatory observations, semi-structured interviews with principals, teachers, and students, and documentary analysis. Data analysis employed Miles et al.’s (2014) framework incorporating data reduction, display, and conclusion drawing, with triangulation ensuring validity. Findings revealed that both schools enhanced student engagement and motivation through IT integration despite infrastructure disparities. SDN Margasari demonstrated systematic management across planning, organization, implementation, and evaluation functions, while SDN Hegarmanah exhibited emergent practices aligned with early adoption stages. Key obstacles included equipment limitations, internet connectivity issues, and variable teacher competencies. Adaptive solutions encompassed phased infrastructure development, targeted professional development, and pedagogical innovation. Results confirm that systematic IT-based learning management can effectively increase elementary students’ learning motivation even within resource constraints when calibrated to institutional capacity. Findings extend Terry’s management theory and motivational frameworks while illuminating developmental progressions in technology integration requiring differentiated support strategies for schools at varying implementation stages.